Predictors of a relapsing course in myelin oligodendrocyte glycoprotein antibody-associated disease - Virupakshaiah, Akash; Schoeps, Vinicius A; Race, Jonathan; Waltz, Michael; Sharayah, Siefaddeen; Nasr, Zahra; Moseley, Carson E; Zamvil, Scott S; Gaudioso, Cristina; Schuette, Allison; Casper, Theron Charles; Rose, John; et al. (Journal of neurology, neurosurgery and psychiatry, 2025)
BackgroundMyelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD) is a recently described demyelinating disorder, and children represent about 50% of all cases. Almost half of the patients experience relapses, but very few studies have evaluated predictors of relapse risk, challenging clinical management. The study aimed to identify predictors at MOGAD onset that are associated with a relapsing course.MethodsProspectively collected data from paediatric patients with MOGAD seen by the US Network of Paediatric MS Centres were leveraged. Univariable and adjusted multivariable models were used to predict recurrent disease.ResultsWe identified 326 MOGAD cases (mean age at first event 8.9 years [SD 4.3], 57% female, 77% white and 74% non-Hispanic) and 46% relapsed during a mean follow-up of 3.9 years (SD 4.1). In the adjusted multivariable model, female sex (HR 1.66, 95% CI 1.17 to 2.36, p=0.004) and Hispanic/Latino ethnicity (HR 1.77, 95% CI 1.19 to 2.64, p=0.005) were associated with a higher risk of relapsing MOGAD. Maintenance treatment initiated before a second event with rituximab (HR 0.25, 95% CI 0.07 to 0.92, p=0.037) or intravenous immunoglobulin (IVIG) (HR 0.35, 95% CI 0.14 to 0.88, p=0.026) was associated with lower risk of a second event in multivariable analyses. Conversely, maintenance steroids were associated with a higher estimated relapse risk (HR 1.76, 95% CI 0.90 to 3.45, p=0.097).ConclusionSex and ethnicity are associated with relapsing MOGAD. Use of rituximab or IVIG therapy shortly after onset is associated with a lower risk of the second event. Preventive treatment after a first event could be considered for those with a higher relapse risk.